2015
DOI: 10.1016/j.celrep.2015.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Cyanobacterial Clock by Synthetically Rewiring Metabolism

Abstract: Summary Circadian clocks are oscillatory systems and allow organisms to anticipate rhythmic changes in the environment. Several studies have shown that circadian clocks are connected to metabolism, but it is not generally clear whether metabolic signaling is one voice among many that influence the clock, or whether metabolic cycling is the major clock synchronizer. To address this question in cyanobacteria, we used a synthetic biology approach to make normally autotrophic cells capable of growth on exogenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Unlike fungal and animal clocks where light is perceived by dedicated photoreceptors, light resetting in cyanobacteria works exclusively via photosynthesis and metabolism [91]. Prior work showed that light-driven changes in energy charge or oxidized quinones are sufficient to reset the clock [92, 93] but did not eliminate metabolism-independent Input pathways.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike fungal and animal clocks where light is perceived by dedicated photoreceptors, light resetting in cyanobacteria works exclusively via photosynthesis and metabolism [91]. Prior work showed that light-driven changes in energy charge or oxidized quinones are sufficient to reset the clock [92, 93] but did not eliminate metabolism-independent Input pathways.…”
Section: Figurementioning
confidence: 99%
“…Prior work showed that light-driven changes in energy charge or oxidized quinones are sufficient to reset the clock [92, 93] but did not eliminate metabolism-independent Input pathways. Pattanayak et al [91] demonstrated that when obligate photoautotrophic strains were engineered to grow in the dark on glucose,, they were rhythmic and blind to light exposure, suggesting that all clock resetting in cyanobacteria works through light-driven metabolism. In the cyanobacterial clock, Output feeds back to Input when the TTFL drives circadian expression of the Kai genes and RpaA, thus supplying non-phosphorylated KaiC in a cyclic manner on a daily basis [94] [95].…”
Section: Figurementioning
confidence: 99%
“…It is becoming clear that the daily shifts in the metabolic state of organisms, ranging from cyanobacteria to mammals, are an important Zeitgeber for their circadian clocks (26,38,39). Recent experiments show that the daily shifts in the cytoplasmic ATP level of the cyanobacterium Synechococcus elongatus are an important cue for the entrainment of its Kai circadian clock (30). To find out how changes in the ATP level affect the Kai oscillator, we compared two widely-used models of the post-translational oscillator, the hexamer model by Van Zon et.…”
Section: Discussionmentioning
confidence: 99%
“…The phase response curve of the Rust model is thus asymmetric: an ADP pulse can induce a much stronger phase advance than a phase delay. However, it was experimentally shown that the phase response curve of the in-vitro Kai system is very symmetric (26,30). When the pulse is given at the moment that leads to a maximum phase delay, then, in all three models, the ADP pulse only slows down the increase of the phosphorylation level.…”
Section: Van Zon and Rust Models Only Show Strong Entrainability At Ementioning
confidence: 99%
“…While there is increasing evidence how the clock is influenced by, and itself influences, photosynthetic light reactions and metabolism, via sensing metabolic activity (Pattanayak et al, 2015) and redox state (Kim et al, 2012) and controlling transcription regulation, the precise evolutionary role of the clock remains insufficiently understood. Elucidating how the circadian clock interacts with other cellular processes and to integrate models of the cyanobacterial circadian clock into a broader cellular context, with the aim to understand how timing mechanisms affect cellular fitness, is a timely question for further computational research.…”
Section: Modeling Phototrophic Growth: An Overviewmentioning
confidence: 99%